1989
DOI: 10.1007/bf01255816
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine and sexual behavior in the male rat: a reevaluation

Abstract: In castrated male rats treated with a low dose of testosterone propionate (0.40 mg/kg per week), the dopamine agonists amphetamine and amfonelic acid reduced mount latency without affecting other aspects of sexual behavior. Apomorphine, in doses between 0.05 and 0.15 mg/kg, and 1-DOPA 5-45 mg/kg + carbidopa 50 mg/kg, lacked effect on sexual behavior. Both amphetamine and amfonelic acid increased locomotor activity in a dose-dependent manner. Apomorphine, in the lowest dose, produced a reduction whereas the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
14
0
2

Year Published

1989
1989
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 36 publications
5
14
0
2
Order By: Relevance
“…For example, it has been reported that exploratory behaviors were much enhanced by amphetamine and amfonelic acid, whereas behaviors directed toward the female, like genital exploration, remained unaffected (Ågmo & Picker, 1990). The inhibitory effects of dopamine antagonists reported in numerous studies can be attributed to motor deficiencies produced by the drugs (Ågmo & Ferna ´ndez, 1989;Ahlenius & Larsson, 1990).…”
mentioning
confidence: 99%
“…For example, it has been reported that exploratory behaviors were much enhanced by amphetamine and amfonelic acid, whereas behaviors directed toward the female, like genital exploration, remained unaffected (Ågmo & Picker, 1990). The inhibitory effects of dopamine antagonists reported in numerous studies can be attributed to motor deficiencies produced by the drugs (Ågmo & Ferna ´ndez, 1989;Ahlenius & Larsson, 1990).…”
mentioning
confidence: 99%
“…However, the number of mounts and intromissions were not affected, suggesting that Meth did not disrupt erectile function. Previous studies examining the effects of acute psychostimulant exposure on sexual behavior have been contradictory and either report the facilitation of sexual behavior (Bignami 1966;Butcher et al 1969) or no effect (Agmo and Fernandez 1989;Agmo and Villalpando 1995). Specifically, acute administration of D-amphetamine (Amph; i.p.…”
Section: Discussionmentioning
confidence: 97%
“…The mean latency to begin mating and the post-ejaculatory interval were not altered by nPGi lesions suggesting that the nPGi is not involved in the expression of these behaviors. Indeed, these behaviors are thought to be under the control of upstream sites (Phillips-Farfan and Fernandez-Guasti, 2009), particularly those associated with MPOA and the mesolimbic dopamine reward system (Agmo and Fernandez, 1989, Hull et al, 1995, Guevara et al, 2008, Kleitz-Nelson et al, 2010). Therefore, nPGi lesions would not be expected to produce any changes in these measures.…”
Section: 0 Discussionmentioning
confidence: 99%